PEMBERDAYAAN PETANI MELALUI BUDIDAYA KOMPOS ORGANIK JERAMI PADI DI DESA SIPUNGGUK KECAMATAN SALO KABUPATEN KAMPAR - Raihana, Raihana; Alfarez, Rizky Deakry; Riyadush, Mohammed Thoyyib Nacrowie; Amelia, Sintia; Faiza, Cindy Aprilya; Sovira, Nurtasya (LPPM Institut Pendidikan Nusantara Global, 2024)
Nearly 80% of Sipungguk Village is an agricultural area producing rice plants in Salo District. Sipungguk Village as a source of rice barns cannot be separated from environmental problems, related to the management of rice straw which is not yet optimal. If left unchecked, this will have an impact on the agricultural environment. Rice straw as rice plant residue after harvest is simply burned or thrown away, this action apart from polluting the air is also a waste of valuable resources. This issue is used as a challenge for students in implementing the 2023 Smart UMRI Real Work Lecture (KKN) by carrying out the work program: